Mo' Money, Mo' Problems: Monetary Motivation Can Exacerbate the Attentional Blink. (April 2015) - Biggs, Adam T; Adamo, Stephen H; Mitroff, Stephen R
The attentional blink (AB) is a compelling psychological phenomenon wherein observers are less likely to identify a second target (T2) when it appears approximately 200 ms after a first target (T1) in a rapidly presented stream of items. The present investigation examined how monetary motivation could impact the AB when participants were differentially motivated to identify T1 versus T2. Participants completed one of three conditions where the only difference across conditions was a motivational manipulation: a standard AB task (control condition), a motivated condition with T1 worth double the points of T2, or a motivated condition with T1 worth half the points of T2 (points in the motivated conditions were linked to a possible monetary bonus). Motivation had an expected influence on overall performance as both motivated conditions had higher overall T1 accuracy relative to the control condition. More specific to the question at hand, the AB was exacerbated (ie T2 performance was worse shortly after T1) when T1 was worth more than T2. This finding suggests that participants overallocated attentional resources to T1 processing at the expense of T2 processing, and it supports current theories of the AB.